Methodological support of economic forecast (in the context of hypothesis of stability and regularity development of phenomena in the temporal space) - Опря, А. Т. (Scientific Progress & Innovations, 2012)
In the article methodological approaches are considered at prognostication of economic indicators taking into account the tendencies of their motion in temporal space of the past coming from hypothetical conception of regularity development of phenomena in the temporal space in the future. Generally speaking about extrapolation of temporal rows on the base of correlationregressive design by the choice of the scientifically grounded line of trend style, as to the mathematical and analytical function which depends on quality of prognosis. Methodical approaches are illustrated the examples of specific calculations.